Student handbook for discrete mathematics with ducks SRRSLEH - belcastro, sarah-marie (A K Peters/CRC Press, an imprint of Taylor and Francis, 2015)
Student Handbook for Discrete Mathematics with Ducks is a Student Reference, Review, Supplemental Learning, and Example Handbook (SRRSLEH) that mirrors the content of the author's popular textbook Discrete Mathematics with Ducks (DMwD) This handbook provides a review of key material, illustrative examples, and new problems with accompanying solutions that are helpful even for those using a traditional discrete mathematics textbook.
"Serious mathematics treated with levity.". - "An A K Peters book.". - Description based on print version record
Keywords: Mathematics -- Textbooks; Mathematics -- Problems, exercises, etc; Computer science -- Textbooks -- Mathematics; Computer science -- Problems, exercises, etc -- Mathematics; Informatique; Mathématiques; Problèmes et exercices; MATHEMATICS; Combinatorics; MATHEMATICS; General; Study guides